The phenomenon of actions and social dynamics of women farm workers in the shallot agricultural system in Enrekang Regency, South Sulawesi - Kasdir Maulana; Andi Nuddin; Irmayani Irmayani (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2025)
The decrease in the number of male workers in the rural shallot agricultural sector, including in Enrekang Regency, has encouraged the increasing role of women as farm laborers. However, their involvement is often faced with a double problem, namely, low levels of education, unequal access to resources, and the burden of domestic roles that go hand in hand with productive responsibilities. This study aims to analyze the socio-economic dynamics of women farm workers, especially related to work motivation, wage system, dual role adaptation strategies, and social relationships with landowners in the shallot farming system. The research method uses a qualitative approach with a case study design in Banti Village, Enrekang Regency, South Sulawesi. Respondents were selected using purposive sampling techniques, consisting of 15 female farm workers (aged 40–60 years) and five productive landowners. Data was collected through semi-structured interviews, participatory observation over two harvest cycles, and document studies, then analyzed using the Miles-Huberman interactive model with source triangulation techniques. The results show that the primary motivation of female farm workers is to meet the economic needs of their families, even though they have a low educational background. The mutually agreed daily wage system is considered fair and capable of creating social stability. In addition, trust-based recruitment patterns, harmonious relationships with landowners, and the provision of non-material benefits strengthen social capital in agricultural communities. Time management strategies and family support, especially from husbands, allow women to remain productive despite taking on dual roles. These findings underscore the importance of gender-responsive and local wisdom-based policies to improve the welfare of women farm workers and the sustainability of small-scale farming systems in rural areas.